Pengaruh Agar-agar dan Jus buah Naga terhadap Kadar Hemoglobin pada Ibu Hamil - Olii, Nancy (Media Kesehatan Masyarakat Indonesia, 2020)
Pregnant women have a high risk of anemia. Iron deficiency is one of the causes of anemia. One alternative to prevent anemia in pregnant women by consuming fruits that contain high iron and vitamin C such as dragon fruit needed to synthesize hemoglobin. This study aims to determine the effect of dragon fruit jelly and juice on the hemoglobin level of pregnant women in the working area of the public health center in the South City of Gorontalo in 2019. The research method used pre-experimental with one group pre-posttest. The population was pregnant women during their second and third trimester of pregnancy with a total of 366 pregnant women. The sampling was conducted through a purposive sampling of 60 pregnant women. Data analyzed with t-test. The results of the bivariate analysis, 87,3% of respondents who consume dragon fruit jelly, a hemoglobin level of them increased with an average 11,08 gr/dL, and 90% of respondents who consume dragon fruit juice, a hemoglobin level of them increased with an average 11,17 gr/dL. The data analyzed applies a t-test which obtains p = 0,001. Consumption of 250 ml dragon food jelly and juice every day for 14 days can raise the amount of hemoglobin in pregnant women.